Design and hot forging manufacturing of non-circular spur bevel gear. (November 2017) - Zhuang, Wuhao; Hua, Lin; Han, Xinghui; Zheng, Fangyan
Highlights: A new design method of NCSB-gear is proposed. A new hot forging process is proposed to manufacture the NCSB-gear. Deformation mechanisms and forging process are comprehensively investigated. Hot forging experiments verify the hot forging process of NCSB-gear. Abstract: Non-circular spur bevel gear (NCSB-gear) is a kind of special spur bevel gear which can perform variable speed ratio transmission. It can achieve several special functions which cannot be realized by circular spur bevel gear (CSB-gear), such as the skid resistance function in automobile differential mechanism. However, NCSB-gear is quite difficult to be designed and manufactured because of its complicated shape and specific transmitting characteristic. In this research, a new design method of NCSB-gear based on vectorial coordinate transmission is proposed to simplify the calculation process of tooth profile, and a NCSB-gear pair which is used in automobile differential is designed. Then, a new hot forging process is proposed to manufacture the driven NCSB-gear, and a pre-forging stage is arranged in this hot forging process so as to pre-allocate the material according to the shape features of the driven NCSB-gear, which is benefit for metal flowing in final forging stage. Several 3D FE simulation models of hot forging process of the driven NCSB-gear with or without pre-forging stage are developed, and the metal flowing, effective strain distribution and temperature distribution are comprehensively investigated and compared. Based on the FE simulation results, several experiments of hot forging process of the driven NCSB-gear are carried out. The results show that, the hot forging process with pre-forging stage can obviously improve the rationality of metal flowing, the homogeneity of the effective strain distribution on NCSB-gear, and the homogeneity of temperature distribution on NCSB-gear and the gear-tooth die. Furthermore, the experiment results are consistent well with the simulation results, and a fully filled NCSB-gear part is obtained by using the hot forging process with pre-forging stage, which confirms that this hot forging process of NCSB-gear is reliable. Graphical abstract: